Increased Stem Cell Marker Expressions during the Peri-Implantation Period in the Rat Endometrium: Constructive Role of Exogenous Zinc and/or Progesterone. (26th May 2014) - Sahin, Cagdas; Yilmaz Dilsiz, Ozlem; Bakti Demiray, Sirin; Yeniel, Ozgur; Ergenoglu, Mete; Demirel Sezer, Ebru; Oktem, Gulperi; Tavmergen Goker, Ege Nazan; Tavmergen, Erol
Abstract : Background . The aim of this study is to determine the effects of zinc and/or progesterone via the expression of α v β 5 integrins and Vitronectins and embryonic stem cell markers during the peri-implantation period. Methods . Four experimental groups were organized. All subjects were mated with males of the same strain to induce pregnancy; after 5 days, zinc and/or progesterone were administered. Blood levels of zinc and progesterone were determined on the sixth day and endometrial tissues were obtained in order to evaluate the immunohistochemical expression of integrins and embryonic stem cell markers. Results . The α v β 5 integrin and vitronectin expression increased in the zinc group compared with the control group and no difference in the progesterone group and zinc + progesterone group. Expression of Klf-4, Sox-2, and c-Myc was found to be increased in the zinc group compared to controls, while no difference was determined between the progesterone, zinc + progesterone, and control groups. Distinctively, expression of the embryonic stem cell marker Oct-4 was increased in all of the experimental groups. Conclusions . Expression of α v β 5 integrin, vitronectin, and embryonic stem cell markers might be increased by the administration of zinc. Our results suggest that zinc could be useful in the induction of implantation rates.